Effects of Corruption and Informality on Economic Growth through Productivity - Bermudez Aparicio, Pedro Daniel (2024)
Corruption and informality are issues which have attracted a great amount of empirical research, since they are variables that can affect economic development in various and complex ways, with direct and indirect effects on economic growth. In this context, the objective of this investigation is to assess the impacts of corruption and informality on economic growth and productivity in countries from Latin America and the OECD (Organisation for Economic Co-operation and Development). To achieve this, a 3SLS-GMM estimation is proposed to manage the endogeneity of the variables in the system of equations. Subsequently, a simulation analysis is conducted to quantify the impacts of increases in corruption and informality on growth and productivity, as well as the influence of human capital in counteracting these impacts. The main findings of the research are as follows: (i) corruption decreases economic growth and productivity in both groups of countries; (ii) informality negatively affects economic growth and productivity; (iii) increases in corruption and informality reduce economic growth and productivity; and (iv) huma